Consumer Preferences and Segmentation Analysis of Bogor Culinary Tourism - Agustina, Ira; Sumarwan, Ujang; Kirbrandoko, Kirbrandoko (Journal of Consumer Sciences, 2017)
This study was conducted to analyze the segmentation & profiling Bogor tourists, analyze consumer preferences towards typical culinary Bogor and the factors that influence them, and formulate appropriate strategies for the development of the typical culinary Bogor. This research used descriptive method survey. Segmentation and profiling analysis performed on the tourist city of Bogor were done with the help of a cluster analysis. For the second objective of this study, this used conjoint analysis to formulate a preference rating of Bogor to the typical culinary travel Bogor. Both of these analyzes were processed using an analysis tool SPSS 16.0. The results showed that there were three groups/ clusters on the tourist city of Bogor. Cluster i.e. one single adult was as much as 23 percent, and cluster of two adult family was as much as 71 percent, and the last cluster of young adults was as much as 6 percent. Traveler preferences resulting from this study were typical culinary areas of Bogor which had complete tourist facilities, ease of sitting, and friendly service. The strategy that can be formulated for the development of the typical culinary Bogor is a breakthrough in terms of marketing, promotion of standardization policy by the government to businesses typical culinary Bogor, as well as the central building typical culinary Bogor.